2022
DOI: 10.3389/fimmu.2022.929089
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Ferroptosis-Related Long Non-Coding RNA Prognostic Signature Correlates With Genomic Heterogeneity, Immunosuppressive Phenotype, and Drug Sensitivity in Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) with high heterogeneity is a common malignancy worldwide, but effective treatments are limited. Ferroptosis plays a critical role in tumors as a novel iron-dependent and reactive oxygen species-reliant type of cell death. Several studies have shown that long non-coding RNAs (lncRNAs) can drive HCC initiation and progression. However, the prognostic value of ferroptosis-related lncRNAs in patients with HCC has not been explored comprehensively. Gene set variation analysis (GSVA) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Finally, 6 lncRNA characteristic models related to ferroptosis were established, most of which have been reported to affect the progression of liver cancer and are associated with poor prognosis, including NRAV [27]. He et al found that ZFPM2-AS1 acts as a miRNA sponge and promotes cell invasion through regulation of miR-139/GDF10 in hepatocellular carcinoma [28], Ma et al Found that DANCR was upregulated in tumor tissues and plasma of patients with HCC, and its expression was highly correlated with microvascular, and liver capsule invasion of HCC [29], MKLN1-AS[30], LNCSRLR [31] and AL137186.2[32] also be associated with the prognosis of patients with HCC, which are consistent with our ndings. Moreover, after correcting for traditional clinical risk indicators, the six-FRLs signature model was shown to be an independent predictive factor for HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 6 lncRNA characteristic models related to ferroptosis were established, most of which have been reported to affect the progression of liver cancer and are associated with poor prognosis, including NRAV [27]. He et al found that ZFPM2-AS1 acts as a miRNA sponge and promotes cell invasion through regulation of miR-139/GDF10 in hepatocellular carcinoma [28], Ma et al Found that DANCR was upregulated in tumor tissues and plasma of patients with HCC, and its expression was highly correlated with microvascular, and liver capsule invasion of HCC [29], MKLN1-AS[30], LNCSRLR [31] and AL137186.2[32] also be associated with the prognosis of patients with HCC, which are consistent with our ndings. Moreover, after correcting for traditional clinical risk indicators, the six-FRLs signature model was shown to be an independent predictive factor for HCC.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we rst identi ed 84 genes and then identi ed 52 signi cant lncRNA associated with ferroptosis. Finally, 6 lncRNA characteristic models related to ferroptosis were established, most of which have been reported to affect the progression of liver cancer and associated with poor prognosis, including NRAV [27], He et al found that ZFPM2-AS1 acts as a miRNA sponge and promotes cell invasion through regulation of miR-139/GDF10 in hepatocellular carcinoma [28], Ma et al Found that DANCR was up-regulated in tumor tissues and plasma of patients with HCC, and its expression was highly correlated with microvascular and liver capsule invasion of HCC [29], MKLN1-AS [30], LNCSRLR [31] and AL137186.2 [32] also have been shown to be associated with the prognosis of patients with HCC, which are consistent with our ndings. Moreover, after correcting for traditional clinical risk indicators, the six-FRLs signature model was shown to be an independent predictive factor for HCC.…”
Section: Discussionmentioning
confidence: 99%
“…LINC01134 can promote Nrf2 recruitment to the GPX4 promoter region via the interaction of the RNA-DNA sequence to increase the transcripts of GPX4, and while LINC01134 silencing leads to oxaliplatin sensitivity by inhibiting the total ROS, lipid ROS, and MDA levels and decreasing the GSH/GSSG ratio ( Kang et al, 2022 ). Guanghao Li et al predicted some ferroptosis-related lncRNAs associating with immunosuppressive phenotype and drug sensitivity ( Li et al, 2022b ). Moreover, in Liu, Z. et al’s research, circRNA cIARS were found to be upregulated in sorafenib-induced HCC cells, which can promote ferroptosis via ferritinophagy by repressing the anti-autophagy effect of ALKBH5 ( Liu et al, 2020 ).…”
Section: Regulation Of Ncrnas Related With Ferroptosis In Cancersmentioning
confidence: 99%